2023
DOI: 10.3390/ani13182832
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Sites for Diagnosis of Leptospirosis in Bovine Anicteric Fetuses

Luiza Aymée,
Maria Isabel Nogueira Di Azevedo,
Luiza Reis
et al.

Abstract: Background: Bovine leptospirosis is an important reproductive disease and abortion is a major sign, leading to economic impacts. Due to its multifactorial etiology, the proper diagnosis of the cause of the abortion is crucial. Necropsy of the fetuses followed by molecular analysis is recommended for diagnosis, and the investigation mainly occurs in the kidneys and liver. This study aimed to analyze unconventional sites for the presence of leptospiral DNA in bovine anicteric aborted fetuses. Methods: Five fetus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…This explains the statistical differences between the spleen and urine and kidney and urine, in relation to positivity. Although the investigation of multiple organs is ideal for the molecular diagnosis of leptospirosis in bovine fetuses [ 37 ], our results indicate that, if it is impossible to collect many samples, the spleen and kidney may be the biological material of choice.…”
Section: Discussionmentioning
confidence: 99%
“…This explains the statistical differences between the spleen and urine and kidney and urine, in relation to positivity. Although the investigation of multiple organs is ideal for the molecular diagnosis of leptospirosis in bovine fetuses [ 37 ], our results indicate that, if it is impossible to collect many samples, the spleen and kidney may be the biological material of choice.…”
Section: Discussionmentioning
confidence: 99%
“…Abortions have been widely associated with bovine leptospirosis, perhaps the most visible sign, being linked to incidental strains when occur as an outbreak, or to adapted strains when occur endemically [44]. It was suggested that abortions by leptospiral infection occur in the final third of pregnancy; however, fetal death has been reported in all stages [45]. The pathogeny of fetal death is also unclear, but the direct infection of the fetuses is the most probable cause.…”
Section: Pathogenesis and Clinical Manifestation In Femalesmentioning
confidence: 99%
“…The abortions infected by incidental strains such as Pomona or Icterohaemorrhagiae usually present icteric and leptospires may be demonstrated in the kidneys and liver [46]. In contrast, anicteric fetuses with hemorrhagic or even presenting no visible lesions are often associated with infection by Sejroe, which may be demonstrated in several organs, such as cardiopulmonary tissue, thymus, subcapsular kidney content, and abomasal liquid [45].…”
Section: Pathogenesis and Clinical Manifestation In Femalesmentioning
confidence: 99%
See 1 more Smart Citation